An efficient low-cost real-time brain computer interface system based on SSVEP - Leow, R.S.; Moghavvemi, M.; Ibrahim, F. (2010)
This paper presents the development of a real-time brain computer interface (BCI) system based on the detection of steady-state visual evoked potential (SSVEP). The system includes a frequency-programmable visual stimulator, EEG-band amplifier and filter, 16-bit data acquisition card, and signal processing and classification algorithms. Three visual stimuli flickering at varying frequencies were shown to the subject, and the system is able to identify the desired target that the subject was focusing on. Experiments on ten healthy subjects using the designed system yielded an average detection accuracy of 86.15. Â© IEICE 2010.